The Effect of Salary Amount on Teachers’ Performance - Rosmanida Rosmanida; Citra Yeni; Esi Delfa Kurnia; Reskina Reskina; Irmi Ningsih; Safrudin Safrudin (International Journal Labs, 2022)
This study aims to determine how big the influence of high and low salaries on teacher productivity and performance. The high and low salaries of teachers are very influential on the performance that has been done. Performance is an important factor in determining the duties and responsibilities of educators. With high performance, the teacher concerned will try to carry out his duties and obligations optimally and work hard and try to face all obstacles, and carry out his duties as well as possible. However, the salaries of private and honorary teachers are not in accordance with the performance they have done. Teacher salaries are still below the standard so that the guarantee of teacher safety and health is reduced, including the length of time it takes for honorary teachers to be appointed as civil servants, which is a problem in the problem of teacher welfare. If the teacher's salary has been appropriately given by the government, there will be no more teachers looking for side work to meet the needs of their families.